Estudo comparativo de comunidades de quirópteros (Mammalia) entre uma ilha costeira e continente no Norte do Brasil - Pathek, Dinah Barbara (2011)
According to the theory of island biogeography, large islands next the mainland tend to have greater richness than the smaller or more remote islands. Moreover, because of the isolation that insular environments suffering, the animals that living there are exposed to various changes, which vary according to the degree of isolation and size of the island. The order Chiroptera is the second largest in number of mammal species, and mobility have critical importance for the survival of some species of this taxon, once it is related to search for habitat and resources such as food and shelter, which can be restricted in the insular environment. This study aimed to compare the structure of existing communities of bats on the Maracá-Jipioca island and in the adjacent mainland. Sampling occurred between February-March (wet season) and September-November (dry season) of 2010. Were sampled 24 points divided into four environments (three points per environment per site - island and mainland). At each point were armed four mist-nets distributed along narrow trails and natural glades, at understory level, which remained open for six hours from sunset. A total of 381 individuals belonging to 26 species from five families were captured. The observed species richness to the island and the mainland did not differ significantly, probably due to the large size of the island and proximity of this with the mainland. But it was possible to verify the existence of a segregation of the communities studied, between island and mainland. However, how bats use different environments as passage, the habitats were not responsible for this differentiation. Thus, a study covering a larger area of the continent, the interior of the Maracá-Jipioca island and different strata of the forest can help clarify the patterns found.